Effect of Sorbitol on Some Physiological and Biochemical Parameters in Diabetic Rats - Baydaa ghanim mohammed. (مجلة الانبار للعلوم البيطرية, 2024)
This study aims to estimate the role of sorbitol consumption in diabetic rats. Sixty male rats were purchased, acclimatized and divided into four groups; negative-control rats were received distilled water, positive-control rats were administered glucose orally, experimental-1 diabetic rats were administered sorbitol 100 mg and experimental-2 rats were administered sorbitol 200 mg orally. After 60 days, sera were collected and tested quantitatively by enzyme-linked immunosorbent assay. Glucose elevation was seen in experimental-2 but not in experimental-1; while insulin was increased significantly in rats of both experimental-1 and experimental-2 but decreased in rats of positive-control when compared to those of negative-control. Although catalase, glutathione peroxidase and superoxide dismutase were decreased significantly in experimental-1, experimental-2 and positive-control, malondialdehyde was elevated significantly in these groups when compared to values of negative-control. For lipid profile, lower high-density lipoprotein were showed in experimental-1 and experimental-2 and more severely in the positive-control than negative-control group; while values of low-density lipoprotein were elevated significantly in positive-control but not in experimental-1 and experimental-2 when compared to negative-control. Values of triglyceride varied insignificantly in experimental-1 and experimental-2; however, they increased significantly in comparison with negative-control but not to positive-control. To our knowledge, this experiment represented the first in vivo study to evaluate the effect of sorbitol on biochemical and biomarkers of diabetic rats. Our findings revealed the safety of sorbitol at low dose but the risk might increase at a higher dose. Therefore, it was necessary to investigate the effects of sorbitol consumption in healthy and diseased individuals.